PENGGUNAAN PREFIKS DALAM BAHASA BUGIS BONE DESA SIMBUR NAIK KABUPATEN TANJUNG JABUNG TIMUR (KAJIAN MORFOLOGIS) - Firman Tara; Cahrawati Cahrawati (Universitas Batanghari, 2021)
This study aims to describe the use of prefix in Bugis Bone language at Bugis Bone Desa Simbur Naik Kabupaten Tanjung Jabung Timur which refers to six types of a prefix, namely prefix ka-, pa-, ma-, ta-, na-, and si-. This type of research is qualitative descriptive. The data in the study is taken from the form of a sentence containing the use of a prefix. The data source is a sentence in Bugis Bone language obtained from the informant. The data collection technique used is a questionnaire. Data is conducted by using Fahmi's theory (2011) related to the use of prefixes. Based on the data analysis, the study results found six types of the prefix used in Bugis Bone language. The six types of the prefix are prefix ka- which can be used in sentences that mean like or often do, prefix pa- used in sentences that function to form nouns or actors, prefix ma- used in sentences that convey as verbs or do something, prefix ta- used in sentences such as word of invitation to the second party, prefix na- serves as subject to practice or action, and the prefix si- serves as a number one. Based on the results of the data analysis, it can be concluded that the prefix used in the most common sentences is the use of the prefix ma- which is meaningful or serves as a verb or doing work. Keywords: prefix use, Bugis Bone, Desa Simbur Naik